2021
DOI: 10.7759/cureus.18148
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Cutaneous Disorders in Patients With Celiac Disease

Abstract: Background and objectiveCeliac disease is an autoimmune multisystem disorder that is triggered by dietary gluten sensitivity in genetically susceptible individuals. It presents with extraintestinal cutaneous manifestations including dermatitis herpetiformis (DH), atopic dermatitis, psoriasis, urticaria, and alopecia areata. Due to the insufficient availability of data, this study aimed to estimate the frequency of cutaneous manifestation in a Pakistani population with celiac disease. MethodsThis cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…While IL-17 blocking agents, e.g., secukinumab and ixekizumab showed promising results in the treatment of psoriasis and PsA, they have the potential to exacerbate Crohn's disease [4]. These observations are consistent with Xi et al [27] (2022) findings which demonstrated that in contrast to other 190 shared signature between psoriasis and UC, IL-17A was only evident in psoriasis transcriptome.…”
Section: Psoriasis and Gastrointestinal Tractsupporting
confidence: 81%
See 1 more Smart Citation
“…While IL-17 blocking agents, e.g., secukinumab and ixekizumab showed promising results in the treatment of psoriasis and PsA, they have the potential to exacerbate Crohn's disease [4]. These observations are consistent with Xi et al [27] (2022) findings which demonstrated that in contrast to other 190 shared signature between psoriasis and UC, IL-17A was only evident in psoriasis transcriptome.…”
Section: Psoriasis and Gastrointestinal Tractsupporting
confidence: 81%
“…While IL-23 has a relatively consistent and unifying role in the pathogenesis of both psoriasis and IBD, inhibition of its downstream effector, namely IL-17A has led to different and paradoxical results in psoriasis and IBD [4]. For example, ustekinumab, a blocking agent of common subunit p40 of IL-12 and IL-23 showed effective inhibition of IL-12/IL-23 pathway and is now approved for plaque psoriasis, PsA, Crohn's disease and UC [16,26,27]. While IL-17 blocking agents, e.g., secukinumab and ixekizumab showed promising results in the treatment of psoriasis and PsA, they have the potential to exacerbate Crohn's disease [4].…”
Section: Psoriasis and Gastrointestinal Tractmentioning
confidence: 99%
“…Skin conditions are a significant contributor to the burden of non-pathogenic disease in all countries and regions globally ( 3 ). Alopecia areata is associated with a higher incidence of other autoimmune diseases, such as autoimmune thyroid disease ( 8 ), pernicious anemia ( 9 ), and celiac disease ( 10 ). Numerous studies also have showed psychological correlates of alopecia areata, including anxiety ( 11 , 12 ), depression ( 11 , 12 ), stress ( 13 ), and social and functional deficits ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by this dermatological feature of CD, researchers are trying to correlate other dermatological and autoimmune diseases with CD, such as psoriasis, alopecia areata, chronic urticaria, cutaneous vasculitis, hereditary angioneurotic oedema and others, although without much success [ 4 , 10 ]. In a study by Dev et al, conducted on 300 coeliac disease patients, the most common skin manifestation of CD was dermatitis herpetiformis (16%), and the second was psoriasis (13.8%) [ 11 ]. To the best of our knowledge, there are only two published reports of chilblains associated with CD [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%